About the immensity of God in Suarez - Hellín, José (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 1948)
Many have shown a desire to know Suárez’s doctrine about the immensity of God. The aim is to respond to this just desire by following the current order in scholastic subjects in the exposition. First, some notions are explained, second the proofs are indicated, third the foundation on the part of God of his relative presence in things is examined and, finally, the very transcendental differences between the immensity or divine location and the created location are pointed out. Consequently, Suárez’s mission of revaluing true doctrines and purifying what is less firm is accomplished, as well as systematizing the demonstrated truths to the extent granted to human understanding.